Review of Tatary-kazakivsostaveOrenburgskogokazach'egovoiska (1748-1917 gg.) by R.R. Aminov. Kazan': Institut istorii im. Sh. Mardzhani AN RT, 2017. 348 p. - Elena V. Godovova; Sergey V. Lyubichankovskiy (RUDN Journal of Russian History, 2022)
-